Luminescence study on crystalline phase of Y2Si2O7 from mesoporous silica and Y2O3: Ln3+ at 900 °C - Amresh I. Prasad; L. Robindro Singh; Rashmi Joshi; R. S. Ningthoujam (AIP Advances, 2018)
Mesoporous silica nanoparticles (mSiO2) have been used in many applications including drug delivery, catalysis, sensing. In drug delivery, tracing of mSiO2 needs incorporation of organic dyes or radio nuclei, etc. However, organic dyes are unstable under various mediums or in longer duration. To overcome this, one of ways is use of lanthanide ions (Ln3+) such as Eu3+, Tb3+ or Dy3+, which show luminescence in visible as well as near infrared (NIR) regions. In this work, nanocomposites of mSiO2 and Y2O3:Ln3+ have been prepared. These are characterized by several techniques. mSiO2 is stable up to 500 °C and microstructure of mesoporous collapses at 900 °C. Interestingly, mSiO2 reacts with Y2O3 to form Y2Si2O7 phase at 900 °C. On the other hand, such phase was not formed from Y2O3 and amorphous SiO2 at same temperature. This finding of the formation of highly crystalline Y2Si2O7 at lower temperature 900 °C is the first report to the best of authors’ knowledge. Their luminescence studies are performed by single or multi doping of Ln3+ ions. Their energy transfer processes are discussed. The crystallinity of Y2O3 or Y2Si2O7 is improved after co-doping of Ce3+ to Ln3+. Such nanocomposites are highly dispersible in distilled water, methanol and PBS (Phosphate Buffered Saline).